Identity Politics In The Campaign Tagline At The 2020 Sumenep Elections - Moh Zuhdi; Moh Ikmal (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2022)
This study wants to find out how the form of identity politics in the campaign tagline in the 2020 Sumenep Pilkada. This research is important to do, considering the messages in the campaign tagline as identity politics in the 2020 Sumenep Pilkada are interesting to study. This study uses a qualitative method. The object of this research is the text and narrative of political campaigns in the taglines "Bismillah Melayani" and "Sumenep Barokah". The results showed that the Sumenep regional election which took place democratically was followed by two pairs of candidates with religious leaders backgrounds, of course, it was a reflection that each of the political parties that carried it really understood the constituent culture, the selection of the taglines "Sumenep Barokah" and "Bismillah Melayani". There are five points in the Sumenep Barokah tagline, namely: First, accelerating, repairing and increasing the infrastructure to support social and economic activities of the community. Second, improving the regional economy, Third, realizing superior human resources. Fourth, create a religious society, and fifth, create good governance. Meanwhile Bismillah Serves on the basis of efforts to facilitate basic needs. Through Bismillah Melayani, religious and service aspects are integrated into the frame of Fauzi-Eva's strength. Keywords: Identity Politics, Tagline, Pilkada